Teachers’ Reflective Thinking Practice: Descriptive Study during COVID-19 in SMP N 2 Singaraja, Bali - Wati, Ni Putu Harista; Myartawan, I Putu Ngurah Wage; Wahyuni, Luh Gede Eka (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
The study aims to analyze the English teachers’ perceptions about reflective thinking in SMP N 2 Singaraja. This research conducted using a descriptive qualitative method. The participants were four English teachers in SMP N 2 Singaraja. The data collection was done through Google form questionnaire that consists of 20 statements in which have five options in each statement such as Always (5), Often (4), Sometimes (3), Rarely (2), and Never (1). Moreover, the teachers should fill in based on their experiences. The results showed that four teachers were in advanced level of reflective thinking teachers. The results of this study are expected to be a baseline for future improvement of reflective thinking during the online learning. Further study is needed because it is only describing on how teachers perceived themselves as reflective thinking in online learning, although this study needs further study in actual action of reflective thinking.